Sistema microcontrolado de acionamento e dimerização de carga elétrica com comandos capacitivos sensíveis ao toque - Peixoto, Marcos Juniti Yonemoto (2018)
This work presents a study and development of an embedded system of dimerization in a DC load through a capacitive touch sensitive. The project incorporates a capacitive touch sensor, communication circuit and a microcontroller programmed in the C language. The steps and stages of development are presented as well as the results obtained from it.